Oxidative and membrane stress-mediated antibacterial activity of WS2 and rGO-WS2 nanosheets - Navale, Govinda R.; Rout, Chandra Sekhar; Gohil, Kushal N.; Dharne, Mahesh S.; Late, Dattatray J.; Shinde, Sandip S. (RSC Advances, 2015)
Graphene-based materials have strong cytotoxic attributes against bacteria due to their unique physicochemical properties. We examined the antibacterial activities of nanosheets of the graphene analogue tungsten disulphide (WS2) and a composite of reduced graphene oxide-tungsten disulphide (rGO-WS2), comparing them with reduced graphene oxide (rGO) by a time and concentration dependent viability assay and growth curve studies against four bacterial strains: Gram negative Escherichia coli (E. coli) and Salmonella typhimurium (S. typhimurium), and Gram positive Bacillus subtilis (B. subtilis) and Staphylococcus epidermidis (S. epidermidis). The nanosheets of the rGO-WS2 composite caused a more significant retardation in bacterial growth and inhibitory effect on the tested bacterial strains than WS2, followed by rGO. The tested E. coli and B. subtilis strains were more susceptible than the other strains. A mechanistic study revealed that rGO and WS2 did not produce the superoxide anion (O-2(-)) or reactive oxygen species (ROS), but the nanocomposite of rGO-WS2 did produce both. However, all these materials did oxidize glutathione, which serves as a redox state mediator in bacteria. We conclude that the antimicrobial mechanism is due to the combined effect of initial cell deposition on the rGO-WS2 materials, the membrane stress due to direct contact with the nanosheets, and the produced superoxide anion-independent oxidation mechanisms. The beneficial aspects of the physicochemical properties of rGO-WS2, such as its size and conductivity, can be precisely customized to reduce its health and environmental risk factors.